2006
DOI: 10.1021/bi061268r
|View full text |Cite
|
Sign up to set email alerts
|

The Latent Promiscuity of Newly Identified Microbial Lactonases Is Linked to a Recently Diverged Phosphotriesterase

Abstract: In essence, evolutionary processes occur gradually, while maintaining fitness throughout. Along this line, it has been proposed that the ability of a progenitor to promiscuously catalyze a low level of the evolving activity could facilitate the divergence of a new function by providing an immediate selective advantage. To directly establish a role for promiscuity in the divergence of natural enzymes, we attempted to trace the origins of a bacterial phosphotriesterase (PTE), an enzyme thought to have evolved fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
321
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 259 publications
(329 citation statements)
references
References 55 publications
5
321
2
1
Order By: Relevance
“…Indeed, promiscuous activities were shown to comprise ample starting points in laboratory evolution experiments performed both in vitro (Khersonsky et al, 2006) and in vivo (Hall, 1999;Miller and Raines, 2005). There also exists evidence (which is inevitably indirect) indicating that promiscuity may have driven the divergence of new receptors (Bridgham et al, 2006) and enzymes (Afriat et al, 2006) in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, promiscuous activities were shown to comprise ample starting points in laboratory evolution experiments performed both in vitro (Khersonsky et al, 2006) and in vivo (Hall, 1999;Miller and Raines, 2005). There also exists evidence (which is inevitably indirect) indicating that promiscuity may have driven the divergence of new receptors (Bridgham et al, 2006) and enzymes (Afriat et al, 2006) in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that organophosphate pesticides are synthetic compounds that have only existed in the environment since the 1950s, the rapid evolution of near diffusion-limited turnover rates in these enzymes is noteworthy. Recent work has shown that their likely evolutionary progenitor is a family of bacterial lactonases that exhibit lowlevel promiscuous phosphotriesterase activity [62].…”
Section: +mentioning
confidence: 99%
“…Interestingly, no naturally occurring substrate has been identified for PTE. 5,6,11 An excellent model to illustrate the last case of promiscuity, product promiscuity, is g-humulene synthase, a sesquiterpene synthase that is known to produce 52 different sesquiterpenes from a sole substrate, farnesyl diphosphate, through a wide variety of cyclization mechanisms. The product distribution can be very sensitive to changes in specific amino acid residues.…”
Section: In˜aki Tun˜o´nmentioning
confidence: 99%